Fungsi Pendidikan Agama Islam dalam Pembentukan Karakter Anak di Era Globalisasi - Radhita Dendha Syouqina (Pusdiklat Tenaga Teknis Pendidikan dan Keagamaan, 2022)
Times are developing, improving the quality of science and technology has also contributed to all aspects of human life with the aim of advancing intelligent society and creating the value of efficiency and effectiveness in all things. However, the development of modern technology in the era of globalization also has many negative impacts such as changes in children's mindsets, lifestyles, perspectives on things, open-mindedness, to things that are not in accordance with the values and norms of applicable regulations, even far from religious teachings. In the midst of these concerns, character education is very much needed in building children's character from an early age to strengthen the foundation they have before meeting new information out there. Islamic religious education becomes a strong pillar in character building by implementing the values contained in it in teaching and learning activities both formally and informally. This study aims to determine how big the role of Islamic religious education in the process of forming children's character in the modern era by using literature research methods. From this study, it was found that Islamic religious education is a strategic effort in realizing the ideal national character starting from the family, institutional institutions and community learning groups which are the main capital for the formation of the nation's character.